Combinatorial magnetron sputtering of AgFeO2 thin films with the delafossite structure. (5th February 2016) - Mao, Fang; Nyberg, Tomas; Thersleff, Thomas; Andersson, Anna M.; Jansson, Ulf
Abstract: The main objective of this study is to demonstrate the strength of the combinatorial approach to rapidly and effectively identify suitable process parameters for the synthesis of AgFeO2 films with layered delafossite structure. ( 00l )-textured delafossite AgFeO2 thin films have been successfully deposited for the first time without post-annealing by magnetron sputtering from elemental silver and iron targets in a reactive Ar–O2 atmosphere. Gradient films with a wide composition range were deposited on single wafers and subsequent screenings of phase- and chemical compositions were employed to optimize process parameters. The optimum deposition temperature for single-phase AgFeO2 growth was 450 °C using a Ag target powered at 15 W with a pulsing frequency of 150 kHz and a Fe target powered at constant 120 W at a total pressure of 4 mTorr and a O2 partial pressure of 0.8 mTorr. Selected films were studied with scanning electron microcopy (SEM), transmission electron microscopy (TEM) and Raman spectroscopy. The optical band gap for the indirect transition in the AgFeO2 film was determined to 1.7 ± 0.1 eV, and the band gap for the direct transition was 2.5 ± 0.1 eV. The film showed insulating electrical properties. Graphical abstract: ( 00l )-textured delafossite AgFeO2 thin films have been successfully deposited for the first time by combinatorial reactive sputtering. Highlights: A combinatorial material science method is used to deposit a complex oxide AgFeO2 . Critical process parameters can be rapidly determined by using this approach. Delafossite AgFeO2 thin film has been successfully deposited for the first time. The experimental band gap of the material has been estimated for the first time. We propose that this approach can be used to design a wide range of delafossites.